Da. Satyendranatha Naskara (Kalakātā : Samakalera Jiyanakathi Prakasana, 2016)
On the life of Satyendranatha Naskara, educator and college teacher from West Bengal.
In Bengali.
Keywords: Naskara, Satyendranātha.; College teachers -- India -- Bengal -- Biography; College teachers; India -- Bengal; Biography